Conditions for coherent vibrations in the cytoskeleton - Pokorný, J (Bioelectrochemistry and bioenergetics (Lausanne, Switzerland), 1999)
Mechanism of organization and order in biological systems is not satisfactorily explained yet. Biophysical theories predicted that coherent endogenous electric field of high frequency can play a significant role in organization. The polarity of vibration structures, spectral energy transfer caused by nonlinearities, and energy supply can lead to energy condensation and excitation of coherent states. These conditions are satisfied in the polymer structures of the cytoskeleton, in particular, in the microtubules as follows from experimental findings. Nonetheless, experimental verification of energy condensation and coherent vibrations in the cytoskeleton is still missing.
Keywords: Electricity; termodynamika; guanosintrifosfát; Thermodynamics; guaninnukleotidy; cytoskelet; elektřina; Guanine Nucleotides; Nonlinear Dynamics; Cytoskeleton; Guanosine Triphosphate; nelineární dynamika